Argument Estimates of Certain Meromorphically p-Valent Functions DeÂ…fined by a Linear Operator (European Journal of Pure and Applied Mathematics, 2017)
Making use of the linear operator Dm , we obtain some argument properties of meromorphically pâˆ’valent functions. Also, we derive the integral preserving properties in a sector.Â